2016
DOI: 10.1097/ede.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose Aspirin, Nonsteroidal Anti-inflammatory Drugs, Selective COX-2 Inhibitors and Breast Cancer Recurrence

Abstract: Background Aspirin, non-steroidal anti-inflammatory drugs (NSAIDs), and selective COX-2 inhibitors may improve outcomes in breast cancer patients. We investigated the association of aspirin, NSAIDs, and use of selective COX-2 inhibitors with breast cancer recurrence. Methods We identified incident stage I–III Danish breast cancer patients in the Danish Breast Cancer Cooperative Group registry, who were diagnosed during 1996–2008. Prescriptions for aspirin (>99% low-dose aspirin), NSAIDs, and selective COX-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
0
23
1
Order By: Relevance
“…Our study of 34,188 breast cancer survivors showed no evidence of decreased recurrence rate associated with postdiagnostic aspirin, NSAIDs, or sCOX2 inhibitor use [13]. Our results were unchanged in stratified analyses and in analyses examining drug exposure and site-specific cancer recurrence.…”
Section: Statinscontrasting
confidence: 59%
See 1 more Smart Citation
“…Our study of 34,188 breast cancer survivors showed no evidence of decreased recurrence rate associated with postdiagnostic aspirin, NSAIDs, or sCOX2 inhibitor use [13]. Our results were unchanged in stratified analyses and in analyses examining drug exposure and site-specific cancer recurrence.…”
Section: Statinscontrasting
confidence: 59%
“…Three cohort studies included patients diagnosed between 1996 and 2003 with follow-up through 2008 [10][11][12]. Later the cohorts were expanded to include patients diagnosed between 1996 and 2008 with follow-up through July 2013 [13][14][15]. Patients diagnosed with metastatic breast cancer were excluded from all studies.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Aspirin has been shown to decrease the risk of breast cancer mortality in some, but not all studies, whereas simvastatin has been consistently associated with a decreased risk of breast cancer recurrence/mortality. Information on prescribed aspirin was available, but it was not possible to account for aspirin bought over the counter.…”
Section: Discussionmentioning
confidence: 99%
“…The drug positively or negatively impact the clinical effect or plasma concentration of another drug even be a significant cause of morbidity and mortality worldwide. Aspirin inhibit the prevention, progression, and metastatic growth of cancer by the inhibition of COX-2 and platelet aggregation ( 34 36 ). The expression of COX-2 is associated with increased cell proliferation and tumor promotion significantly.…”
Section: Discussionmentioning
confidence: 99%